Monitoring Kadar Gas Berbahaya Pada Kandang Ayam Dengan Menggunakan Protokol HTTP Dan ESP8266 - Muhamad Nur Arifin; Mochamad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In this research, Authors make a monitoring system of dangerous gas content in the chicken coop. The system able to inform air quality in the form of ammonia and methane gas contained in chicken coop and give result of reading of gas data which considered dangerous to worker in chicken coop and can be seen by platform. The system generally consists of two gas sensors, the MQ 135 sensor to detect the ammonia, and the MQ 4 sensor to detect methane, and connect to the internet network via the ESP8266 modul with Arduino Uno microcontroller that aims to upload sensor data to web Thingspeak and displayed in the form of graphs as a means of information on the chicken coop. Testing was did with 3 stages of connectivity, functionality, and delay. The connectivity test proves that the ESP8266 can connect to the Access Point and Internet network. The functionality test proves that the sensor can read the gas and retrieve the data. And the last is the delay test, which is calculating the length of the process from the beginning of the sensor readings until the data arrived at IoT web based Thingspeak. From the results of calculations that have been done in testing, it is found that the time required for a single data transmission takes as much as 5-19 seconds. The time may change because there are aspects that can hamper such as internet connection, the number of devices connected to one network internet, but the purpose of research is in accordance with expectation.